Somatic Embryogenesis in Coffee: The Evolution of Biotechnology and the Integration of Omics Technologies Offer Great Opportunities - Campos, Nádia A.; Panis, Bart; Carpentier, Sebastien C. (Frontiers in Plant Science, 2017)
One of the most important crops cultivated around the world is coffee. There are two main cultivated species, Coffea arabica and C. canephora. Both species are difficult to improve through conventional breeding, taking at least 20 years to produce a new cultivar. Biotechnological tools such as genetic transformation, micropropagation and somatic embryogenesis (SE) have been extensively studied in order to provide practical results for coffee improvement. While genetic transformation got many attention in the past and is booming with the CRISPR technology, micropropagation and SE are still the major bottle neck and urgently need more attention. The methodologies to induce SE and the further development of the embryos are genotype-dependent, what leads to an almost empirical development of specific protocols for each cultivar or clone. This is a serious limitation and excludes a general comprehensive understanding of the process as a whole. The aim of this review is to provide an overview of which achievements and molecular insights have been gained in (coffee) somatic embryogenesis and encourage researchers to invest further in the in vitro technology and combine it with the latest omics techniques (genomics, transcriptomics, proteomics, metabolomics and phenomics). We conclude that the evolution of biotechnology and the integration of omics technologies offer great opportunities to (i) optimize the production process of SE and the subsequent conversion into rooted plantlets and (ii) to screen for possible somaclonal variation. However, currently the usage of the latest biotechnology did not pass the stage beyond proof of potential and needs to further improve.